VD CODICNICATIONS VOTES LYD CO, TH STUDIES IN JIES IN THE THEORY OF MANAGEMENT FAYOL AND TAYLOR (Comparative View) - Bu'Era, Abu-Bakr M. (Dirasat in Economics and Business, 1969)
"Thrvaghout the who the military type shandoned and wher w the whole field of management of organization should be and what may be called the functional substituted in its place." (TAYLOR) 1911 For any action whatsoever, employee should receive orders from one superior only... Shoald (unilty of Command) be violated, aathority is undetermined, discipline is in jea pardy, order disturbed, and stability threatened." (FAYOL) 1916 Varch 20. 1856 is one of the greatest days in the history of isiness management ; that day witnessed the birth of a great man whose tomb, at German-town, Pennsylvania, bears the inscription *Father of Scientific Management ;" 1 it was Frederick Winslow Taylor whose writings are considered the first most recognized attempt of formulating a theory of management with definite principles and rules. His work became so famous to the extent that some following manage ment scholars commented on it by saying that “no man, born of woman, can do more.” 2 0 * Assistant Lecturer, Department of Business Administration, Faculty of Econo mics and Commerce, University of Libya. 11) Lyndall F. Urwick, The Life and Work of Frederick Winslow Taylor (London : Urwick, Orr and Partners, Ltd., p. 1. (2) Ibid., p. 12. THE LIBYAN ECONOMIC AND BUSINESS REVIEW in his time, ganizations and Despite this fact Taylor's ideas were not appreciated, in hisia in the United States, he was attacked by labor organizations business leaders ; he was brought in front of a special House commit on January 25, 1912 to deliver a testimony of 287 pages to defe his ideas. Taylor was a practical man and within just twelve vean starting as an ordinary laborer, he became the general manager of th' Manufacturing Investment Company. 3 Contemporary to Taylor was another eminent student of manage. ment, Henry Fayol (1841-1952), whom many scholars consider as “the real father of modern management theory."4 Fayol, like Taylor, was an engineer. He had a very successful career ; when he was appointed as managing director of the Commentry-Fourchambault in 1888, it was on the verge of bankruptcy ; when he retired he left it with an unattac kable financial position and an exceptional staff quality. 5 Fayol emphasized that the company's success was not due to any extraordi. nary personal qualities, but to the proper application of certain simple administrative principles. 6 Fayol and Taylor met each other, yet their ideas were almost identical. Some management authorities consider Fayol's book Administration Industrielle et Générale ? which was published in 1916, the year following Taylor's death, as "the complement to Taylor's work.” 8 However Fayol noticed that Taylor's ideas were not widely applied in France because “... their effective application required the (3) Ibid., p. 5. (4) Harold Koontz and Cyril O'Donnell, Principles of Management, 4th ed. (McGrat Hill Book Company, 1968) p. 21. (5) L. Urwick in his foreword to : Henry Fayol, General and Industrial Manage ment (London: Sir Isaac Pitman and Sons, Ltd., 1949) P. vii. (6) L. Urwick, The Pattern of Management (Minneapolis : University of Minnesota Press, 1956) p. 45. (7) As can be noted in the above footnote the word "administration" that Fayo originally used has been translated into "management" and I do not see any necessity for such a change. (8) Urwick, The Pattern of Management, op. cit., p. 45.